Pemikiran Teologis Martin Luther Mengenai Pendidikan Iman Anak - Riska Pawarranganu; Yusni Simon Tonapa; Desryanty Runde Bara Padang; Lexsi, Lexsi; Ronaldo Stefanus (Lembag, 2025)
This article examines Martin Luther's theological thinking on children's faith education as part of Reformation theology. Luther emphasized that the family is a small church (ecclesiola), making parents the first and primary faith educators for children. In his understanding, faith education must begin early, be carried out repeatedly, be realized through example, and be based on the use of the Small Catechism as the primary tool of spiritual education. This paper analyzes the theological and practical aspects of Luther's thought and their relevance to the context of children's education today. This paper aims to explore in depth Martin Luther's theological thinking on children's faith education, his theological background, the principles of faith education according to Luther, and their implications for contemporary Christian education. This research uses a library research method with a theological-historical approach. The primary sources are Martin Luther's writings on education, the family, and the church. Secondary sources include books, journal articles, and contemporary theological analyses of Luther's faith education.